Efektivitas Metode Jigsaw Dibandingkan Metode Make a Match dalam Pengetahuan Personal Hygiene Saat Menstruasi: Studi Literatur - Ambo Sengngeng; Herinawati Herinawati; Vivin Dianty; Iksaruddin Iksaruddin (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Adolescents have problems related to personal hygiene at puberty due to a lack of knowledge of explanations and health services. Poor personal hygiene habits and can lead to reproductive tract infections. This literature study is to analyze the effectiveness of the jigsaw method compared to the make a match method in the knowledge of personal hygiene on menstruation in young women. The search results obtained were 8 journals and articles which were considered to have the same objectives as the research title. As for the journal review before being given a jigsaw, after being given a jigsaw, before being given a make a match, after being given a make a match. The results of the review of the research journal stated that the second method was more effective, namely the make a match method compared to the jigsaw method, seen from the increased knowledge of adolescents after being given counseling on reproductive health, personal hygiene during menstruation, and increasing significantly on the assessment graph with a statistical value before being given a jigsaw value of 37, 4%, after being given a jigsaw the statistical value of 73.5%, before being given a make a match 73.8%, after being given a make a match the statistical value increased by 75.8%. Based on the review of journals, the make a match method is more effective with the result that the statistical value of 75.8% increases as seen from the increase in respondents' knowledge. In providing reproductive health education about personal hygiene during menstruation for adolescents, the make a match method can be used.